Ntak Awo Dance in the Social Life of the Kerinci Community - Munawaroh, Anisa; Sari , Ayuthia Mayang (Universitas Negeri Medan, 2025)
The Ntak Awo Dance is a traditional performing art originating from the Hamparan Rawang area, Sungai Penuh City, Jambi Province. Initially, this dance functioned as part of a traditional ritual, but over time it has undergone a transformation into an entertainment dance popularized by a local artist named Arwati. This article aims to describe the form, function, and cultural meaning of the Ntak Awo Dance as a representation of the identity of the Rawang community. The research method used is descriptive qualitative with an ethnographic approach through field observations, in-depth interviews, and literature studies. The results show that the Ntak Awo Dance is performed in various social events such as weddings, cultural festivals, community activities, and official state events. This dance is usually performed with energetic musical accompaniment, distinctive poetry or rhymes, and a